Seroprevalence of viral hepatitis B, C and E in TB patients from the Republic of Moldova - Octavian SAJIN; Constantin SPINU; Maria ISAC; Nina IZIUMOV; Aliona CHERNIAVSKA; Alexandru BUGA; Sergiu BRENISTER (One Health & Risk Management, 2023)
Introduction. For the first time, in the Republic of Moldova, there was established the seroprevalence of viral hepatitis B, C and E markers in patients with tuberculosis depending on gender, age and geographical areas.